An operational feasibility on City Delivery a food runner company - Masangya, Chenille B.; Medel, Krichelle Bernadette D.; Reyes, Stella Maris B.; Tan, Adelene Joyce N.
City Delivery is a third-party delivery service provider based in the Philippines. The company delivers food and non-food items and even groceries to home-based customers and corporate employees from Manila's best restaurants and food establishments. The products are delivered to customers through delivery waiters riding in motorcycles. At present, City Delivery has over 420 merchant partners in Metro Manila and Cebu. The company has different ordering options to provide convenience to its customers. These options range from website portals, online and mobile applications, and landline or phone calls. City Delivery also allows multiple payment options for faster transactions. The company currently has 151 employees, 78 of them are riders assigned all over Metro Manila at different station points. At present, the company receives an average of 400 orders per day. City Delivery is composed of the Human Resource and Administration, Operations, Accounting and Finance, Sales and Marketing, and Information Technology Divisions. This study is focused on the company's Operations division - order processing up to delivery. Also, only the major concerns of Metro Manila operations will be given priority and not those in Cebu City. The Operations division is divided into 2 functional groups: the CSR (Customer Service Representatives) and the Logistics. The CSR is responsible for accepting and processing customer order while the Logistics is in-charge of assigning who among the riders will pick up the order from the restaurant/shop and deliver it to the customer. The CSR group is composed both of inbound and outbound CSRs. Inbound CSRs are those that receive orders from the customers. Outbound CSRs, on the other hand, are those that forward orders to the partner establishment and call customer for alternative items if an order item is unavailable. Currently,the company has 13 inbound CSRs (at least 11 have shift in a day) and 5 outbound CSRs (at most 3 have shift in a day). Each day, the company receives around 14, 365 calls, 93% of them are answered calls, and only around 36% of the answered calls generate sales. City Delivery's ultimate goal at the end of each day is to ensure 100% on-time and successful delivery to their customers. However, with their current system performance and as their partner vendors and customers grow, late deliveries became inevitable in their daily operation. Currently, the process of confirmation to delivery alone takes around 55 minutes to be processed. To analyze the root cause of late deliveries, five main factors were identified and fleshed out: people, methods/procedures, equipment, environment, and materials. Problems related to people are lack of riders to deliver the orders, human errors such as wrong order taking or picking-up of wrong item from the merchant, and riders being lost. Problems in methods/procedures include poor dispatching, and unsatisfactory manpower plotting. Problems in materials include having incomplete orders caused by either incomplete food prepared by the partner vendor or some items were not picked-up by the delivery waiter, delayed food preparation by partner vendors, and food mishandling. Having unreliable motorcycles because of lack of proper maintenance composes the problem in equipment. Lastly, heavy traffic that is usually beyond anyone's control is an environmental factor causing a late delivery. Looking into the company's records of customer complaints revealed the following to be the major causes of late deliveries: 1. Late arrival of delivery notice {40.00%} - sometimes riders receive delivery details from the dispatcher too late such that they will not make it at the specified pick-up and delivery time; 2. Multiple deliveries (29.41%) - the number of available riders is too low compared to the arrival of orders such that they can hardly deliver all orders on time; 3.Incomplete orders (11. 76%) - there are missing items in the customer's orders or missing essentials such as utensils, etc. Based on the company's records, this is almost always, if not always, a mistake of the restaurant. As a solution to these problems, alternatives in the Operations division's process flow were recommended and evaluated. Basically, the recommended changes in the process flow included the use of GPS-technology in determining the travel time between locations so that the promised time of arrival of customer's order is what is actually achievable by the rider, given the distance and traffic situation. Also, an additional step involving the checking of ordered items was included in both alternatives. To address the major causes of late deliveries, particularly the late arrival of delivery notices, the proponents of the study suggested the addition of 2 outbound CSR agents. At present, the capacity of the current workforce is only 40.73% of the total orders during peak hours. The feasible optimal number of outbound CSR agents was determined. The solved financially optimal number of outbound CSR was 5. To address the problem on lack of riders due to high rate of order arrivals on Sundays, at least 2 delivery waiters scheduled on Monday to Thursday will be transferred to a Sunday peak hour -shift.